Analysis Selling Price at MSMEs Rempeyek Nok Uus - Ayu Anisa; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Westscience Press, 2024)
This study aims to investigate the product pricing process at the UMKM Rempeyek Nok Uus using the Cost Pricing strategy. The methodology applied is quantitative with descriptive analysis. The primary data source in this study comes from direct interviews with the owner of the UMKM Rempeyek Nok Uus. The findings of this study reveal that the prices set by this UMKM Rempeyek Nok Uus tend to be lower than those that would be set using the Cost Plus Pricing method. This occurs because the UMKM does not carry out detailed cost calculations but only bases its calculations on rough estimates. As a result, when using the Cost Plus Pricing method, which adds a 20% Margin, the resulting price becomes IDR 20,000, while the UMKM sets the price based on an estimate of around IDR 15,000 to IDR 15,500. This finding indicates that using Cost Plus Pricing with the planned Margin addition could be more profitable.